Strandless rolling based on four-high modules in stands of continuous section mills - L. Oginskiy; O. Hrechanyi; T. Vasilchenko; A. Vlasov; Y. Torba (Journal of Alloys and Metallurgical Systems)
When rolling in forks without grooves, the most problematic problem continues to be to ensure the stability of the rolling in the rolls and between the stands. The analysis was carried out and recommendations were developed for improving the technology and equipment for roughing groups of stands of continuous mills, intended mainly for rolling simple sections. A technology has been developed that includes the use of four-roll modules formed by two pairs of rolls for rolling stock reduction in two mutually perpendicular directions. Rolls of one of the pairs are non-driven and they are mixed in the direction of rolling, deformation in them is carried out due to the support of the driven rolls. Non-driven rolls are deforming and at the same time perform the function of the outlet mating reinforcement, ensuring the stability of the roll in the rolls. The four-roll module was created on the basis of the author's developments used in section mills and intended for the formation of four-roll calibers in the operating duo stands. In the four-roll deformation zone formed by the module, a stress state diagram is created, which is close to all-round compression. This ensures an increase in the roll-out of surface defects of the deformed metal. Experimental studies have confirmed that defects roll out as 40–50 % more intensively in a four-roll deformation zone than in a box one. The equipment and method for caliber-free rolling in the roughing group of stands of continuous light section mill 250 have been developed.